Cultural Traditions of Khanduri Blang in Reubee Village Aceh, Indonesia - Arifin, Muhammad; Manan, Abdul (Jurnal Ilmiah Peuradeun, 2018)
Before Islam was introduced into Aceh, many people there still believed in animism or dynamism or Hinduism or Bhudhism. Some parts of those beliefs still affect the local Acehnese cultures even after most of the people have become Muslim. This study describes the ritual of Khanduri Blang, as an acculturation of the people from Reubee village and surrounding villages in Pidie District between their previous cultures with their new Islamic culture: The study also looks at the reasons why the people from Reubee still perform these rituals in recent times. A religious anthropological approach was used to get plenary data about the subject. The data was collected using observations, interviews, and study of related literature. The results showed that the people living in that area performed the rituals as they believed that they would prevent dangers and harm from ghosts and spirits that live around their rice fields. Even though the people have been acculturated to Islam they still perform these ceremonies since they have been handed down as part of their culture and they still do not have sufficient comprehension of the tenets of Islam. Furthermore, the involvement of their local religious figures in the ceremonies convinces the people that these rituals do not contradict their Islamic beliefs. Then too, the use of local traditions as a medium for introducing Islam brought the understanding that such rituals were part of the traditions of Islam.